2021
DOI: 10.1007/s10750-021-04646-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects and cost-benefit analysis of eight spawning gravel augmentations for Atlantic salmon and Brown trout in Norway

Abstract: River regulation alters flow and sediment regime, habitat availability, and ultimately the ecological functioning of rivers. Various restoration and mitigation measures have been developed to improve ecological function, and among them is the addition of gravel to enhance the reproduction of gravel bed spawning fishes. However, information on long-term efficiency, costs, and maintenance needs of gravel additions are scarce. Here, we study the functioning of gravel additions at eight sites in three rivers in we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…Ecological restoration frequently focuses on providing habitat and reducing density‐dependent mortality of prey whose abundance is limited by suitable refuge. For juvenile Atlantic salmon, refuge in gravel interstitia, undercut banks and woody debris is important and thought to limit predation risk and restoration efforts have shown that remediating these habitat features can increase juvenile densities (Pulg et al 2022). Direct tests have demonstrated that increased habitat complexity reduced predation (Miyamoto et al 2021).…”
Section: Addressing Major Ecological Questions With Predator–prey Tag...mentioning
confidence: 99%
“…Ecological restoration frequently focuses on providing habitat and reducing density‐dependent mortality of prey whose abundance is limited by suitable refuge. For juvenile Atlantic salmon, refuge in gravel interstitia, undercut banks and woody debris is important and thought to limit predation risk and restoration efforts have shown that remediating these habitat features can increase juvenile densities (Pulg et al 2022). Direct tests have demonstrated that increased habitat complexity reduced predation (Miyamoto et al 2021).…”
Section: Addressing Major Ecological Questions With Predator–prey Tag...mentioning
confidence: 99%
“…Similarly, Hesthagen et al (2011) presented the case for liming acidified rivers to restore water quality, resulting in Level 3 success for 13 Norwegian rivers where fisheries are now active and able to draw from the harvestable surplus. Direct improvements to spawning habitat by addition of gravel were highly successful (Barlaup et al, 2008;Pulg et al, 2021), as were instream enhancements to create shelter for juveniles (MacInnis et al, 2008;Floyd et al, 2009), including de Jong and Cowx (2016) where benefits persisted for at least 20 years following addition of boulders and V-dams in Downloaded from https://academic.oup.com/icesjms/advance-article/doi/10.1093/icesjms/fsab201/6425092 by guest on 13 November 2021…”
Section: Successmentioning
confidence: 99%
“…Thus it is important to evaluate the efficiency and perform cost-benefit analyses of the practices. Pulg et al (2021) monitored the long-term effects of spawning gravel augmentations in three rivers in western Norway and concluded that the measures had long life span (up to 18 years) at relatively low cots (1.05 € m 2 -year -1 ), and significantly increased Atlantic salmon and brown trout (S. trutta (Linnaeus, 1758)) reproduction. The three Norwegian rivers presented in the paper covered a range of average discharges and design floods, and provided information on the lifespan of the gravel adjustments under different flow conditions.…”
Section: Lessons From Norwaymentioning
confidence: 99%
“…To accomplish that, studies will increasingly need to move from evaluating the immediate presentday impacts of hydropower production, to studying effects over the longer term on populations and communities (Bradford, 2021), in part because of the lag effects associated with many of the direct effects of hydropower development. Only with the availability of good multiple endpoint data can we hope to ensure the development of appropriate adaptive and integrative resource management strategies that include effective, cost-efficient mitigation measures (Bett et al, 2021;Haraldstad et al, 2021;Pulg et al, 2021). Thus long-term data sets will become increasingly important for the sustainable management and mitigation of hydropower effects, especially in multispecies systems (Bett et al, 2021;Katopodis, 2021).…”
Section: Synopsismentioning
confidence: 99%